SELECTION OF A SYSTEM OF INDICATORS CHARACTERIZING THE EFFECTIVENESS OF THE FLIGHT SAFETY MANAGEMENT SYSTEM - Kharchenko, Volodymyr; Pechevysty, Ruslan; Alexeiev, Oleh; Karapetyan, Serob (Proceedings of National Aviation University (archive), 2020)
The article poses the task of evaluating the system of indicators itself with such a mathematical apparatus that would allow expressing by number the overall efficiency of the SMS for the required period of time or its potential capabilities in a form suitable for use in managing the relationship between production activities and the system of indicators, i.e., required development of a specialized mathematical apparatus for evaluating the effectiveness and a specialized environment in the form of a software product - information monitoring of SMS